Numerical modelling of backward front propagation in piping erosion by DEM-LBM coupling. Issue 7 (3rd August 2017) - Tran, D.K.; Prime, N.; Froiio, F.; Callari, C.; Vincens, E.
Abstract: A granular soil REV located on the upstream side of the erosion pipe front is modelled numerically, at the grain scale, by coupling the Discrete Element Method (DEM) with the Lattice Boltzmann Method (LBM) for the representation of the solid and fluid phases, respectively. The implementation of DEM follows a standard molecular dynamics approach and the interactions between grains are regulated by unilateral contacts and breakable bonds. A synopsis of the LBM scheme is provided, with focus on the implementation of non-slip conditions for moving boundaries and use of the Multiple Relaxation Time approach for improved numerical stability. The coupling scheme is described along with the criteria for setting the numerical parameters of the two methods. After a "dry" preparation procedure, the numerical REV is tested under fully saturated conditions and increasing pressure difference. Backward erosion is observed and a micromechanical inspection of the granular phase suggests that arching through force chains and the breakage of tensile bonds are prominent resistance and degradation mechanisms, respectively.